Accomplishing comprehensive development of personality through educational process - Ponikarovska, S. V.; Понікаровська, С. В.; Поникаровская, С. В. (Харківський національний автомобільно-дорожній університет, 2020)
The article deals with the main principles of students’ social adjustment during their studies at the university and analyzes what influence this process has on the development of their creative activity and how it forms their personality. The article emphasizes that the process of education accomplishes the comprehensive development of the student’s personality and prepares them to be active participants of social life as well as competent specialists in engineering.
Всебічний розвиток особистості у процесі освіти
Всестороннее развития личности в процессе образования
Keywords: assimilation; social adjustment; individual; communication; interaction; асиміляція; соціальна адаптація; індивід; спілкування; взаємодія; ассимиляция; социальная адаптация; личность; общение; взаимодействие; 378.147